Effect of algae bloom on seawater reverse osmosis (SWRO) desalination process with gravity-driven membrane (GDM) pre-treatment - Tan, Zi Qi (Nanyang Technological University, 2020)
Water scarcity has been a chronic issue that many countries worldwide are trying to address. Coupled with the effects of global warming, which affects the water cycle, countries continue to find ways to meet their population’s water demand. Currently, seawater reverse osmosis (SWRO) continues to be the most popular desalination technology used, accounting for 84% of the total desalination plants operating globally. However, membrane fouling continues to be an inevitable problem in many SWRO applications and hence pre-treatment of the seawater is required to mitigate this. Recently, gravity-driven membrane (GDM) filtration technology has been gaining increasing attention due to its low energy usage, chemical-free treatment process, where biofilms are allowed to be developed on the membrane surface. Instead of applying pressure for feed water to pass through the membrane in conventional membrane-based treatment processes, gravity force is used as the driving force, thus saving much energy. Recent studies have shown its potential in producing superior permeate water quality and reduce RO membrane fouling in SWRO pre-treatment process. The increasing occurrence of algal blooms in the sea has become a threat to SWRO desalination plants due to its potential to cause serious membrane fouling problems. This puts into question the ability of GDM to mitigate SWRO membrane fouling under this context of seawater algae bloom. Hence this study aims to find out the effect of seawater algae bloom on RO membrane fouling, with GDM as the pretreatment by monitoring the SWRO flux and membrane performance through a series of RO membrane autopsy tests. An analysis of the RO membrane flux was done over a 15-day period with the Thalassiosira pseudonana algae cells in spiked in seawater and feed into the GDM system. Results have shown that this leads to a decline in RO flux. Membrane autopsy tests are performed to identify the factors affecting this, but the results are not conclusive.